Using Lean Management to Reduce Emergency Department Length of Stay for Medicine Admissions. Issue 2 (April 2017) - Allaudeen, Nazima; Vashi, Anita; Breckenridge, Julia S.; Haji-Sheikhi, Farnoosh; Wagner, Sarah; Posley, Keith A.; Asch, Steven M.
Abstract : Background: The practice of boarding admitted patients in the emergency department (ED) carries negative operational, clinical, and patient satisfaction consequences. Lean tools have been used to improve ED workflow. Interventions focused on reducing ED length of stay (LOS) for admitted patients are less explored. Objective: To evaluate a Lean-based initiative to reduce ED LOS for medicine admissions. Design, Setting, Patients: Prospective quality improvement initiative performed at a single university-affiliated Department of Veterans Affairs (VA) medical center from February 2013 to February 2016. Intervention: We performed a Lean-based multidisciplinary initiative beginning with a rapid process improvement workshop to evaluate current processes, identify root causes of delays, and develop countermeasures. Frontline staff developed standard work for each phase of the ED stay. Units developed a daily management system to reinforce, evaluate, and refine standard work. Measurements: The primary outcome was the change in ED LOS for medicine admissions pre- and postintervention. ED LOS at the intervention site was compared with other similar VA facilities as controls over the same time period using a difference-in-differences approach. Results: ED LOS for medicine admissions reduced 26.4%, from 8.7 to 6.4 hours. Difference-in-differences analysis showed that ED LOS for combined medicine and surgical admissions decreased from 6.7 to 6.0 hours (−0.7 hours, P = .003) at the intervention site compared with no change (5.6 hours, P = .2) at the control sites. Conclusions: We utilized Lean management to significantly reduce ED LOS for medicine admissions. Specifically, the development and management of standard work were key to sustaining these results.